Historical thinking about sources in the context of a standards-based curriculum: a Swedish case. Issue 4 (1st October 2016) - Samuelsson, Johan; Wendell, Joakim
ABSTRACT: The increased interest in basing teaching on disciplinary thinking has had a profound impact on the syllabus for history in Sweden. Within this context, we examine how students demonstrate one aspect of disciplinary thinking in history, namely reasoning about historical sources. The material used is written answers to an assignment about historical sources in the national test in history for year 6. The analysis shows that many students are able to show at least some aspects of disciplinary thinking about sources, though the vast majority has problems with contextualising the source in the assignment. One explanation put forth is that the syllabus is not yet fully enacted in teaching practices.